2020
DOI: 10.3390/ijms21249596
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Cartilage Using a Random Positioning Machine

Abstract: Articular cartilage is a skeletal tissue of avascular nature and limited self-repair capacity. Cartilage-degenerative diseases, such as osteoarthritis (OA), are difficult to treat and often necessitate joint replacement surgery. Cartilage is a tough but flexible material and relatively easy to damage. It is, therefore, of high interest to develop methods allowing chondrocytes to recolonize, to rebuild the cartilage and to restore joint functionality. Here we studied the in vitro production of cartilage-like ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 89 publications
7
21
0
Order By: Relevance
“…As expected, the wet weight of engineered constructs in the CHP group was the highest among the three treatment groups since the GAG is a major water-binding component of cartilage (KIANI et al, 2002). The ratio of COL2A1 to COL1A2 has also been used to evaluate chondrogenic capacity (Wuest et al, 2018;Wehland et al, 2020), and in our results, CHP substantially increased the COL2A1/ COL1A2 ratio compared to SMG groups. Although upregulation of type II collagen deposition and COL2A1 expression was observed in the SMG groups compared to static controls, the magnitude of upregulation was not less than in the CHP groups.…”
Section: Genesupporting
confidence: 83%
See 1 more Smart Citation
“…As expected, the wet weight of engineered constructs in the CHP group was the highest among the three treatment groups since the GAG is a major water-binding component of cartilage (KIANI et al, 2002). The ratio of COL2A1 to COL1A2 has also been used to evaluate chondrogenic capacity (Wuest et al, 2018;Wehland et al, 2020), and in our results, CHP substantially increased the COL2A1/ COL1A2 ratio compared to SMG groups. Although upregulation of type II collagen deposition and COL2A1 expression was observed in the SMG groups compared to static controls, the magnitude of upregulation was not less than in the CHP groups.…”
Section: Genesupporting
confidence: 83%
“…On the contrary, prolonged mechanical unloading by space flight has been shown to accelerate cartilage degeneration (Herranz et al, 2013;Fitzgerald, 2017;Fitzgerald et al, 2019). Although several studies suggested that SMG was beneficial for preserving a chondrogenic phenotype through induction of 3D aggregates from monolayer cultures (Aleshcheva et al, 2015;Wuest et al, 2018;Wehland et al, 2020) and promoted cartilaginous components deposition for scaffold cultures (Freed and Vunjak-Novakovic, 1997), the degree of hypertrophic TABLE 3 | Key enriched KEGG pathways and associated differentially expressed genes (DEGs) in CHP and SMG groups as compared to static controls within female and male donor cohorts. *q < 0.05, **q < 0.01, ***q < 0.001 represent statistical difference of the two groups in each fold change value.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prolonged exposure to no load is known to affect regenerative growth and tissue repair by impairing adult stem cell proliferation and differentiation processes (Blaber et al, 2014). The negative impact of microgravity and ground-based simulation conditions on physiological systems has been confirmed by numerous studies, which report skeletal muscle cell atrophy, inhibition of osteoblast differentiation, reduction in osteoblast number, altered immune cell activation, and abnormal chondrocyte formation as the main harmful effects on cellular function (Nabavi et al, 2011;Chatziravdeli et al, 2019;Wehland et al, 2020;Ludtka et al, 2021). Based on this evidence and taking our previous work as a starting point (Tarantino et al, 2020), we have here evaluated the efficacy of anti-MSTN antibodies in preventing muscle degeneration induced by RPM exposure in primary cultures of human satellite cells, reproducing identical experimental conditions and enriching previously obtained data.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that long-term µg created by RPM-induced 3D growth in human chondrocytes. The tissue-engineered spheroids without any scaffolds showed no signs of apoptosis and the typical cartilage morphology [18].…”
Section: Breast Cancer Cells In Microgravity: New Aspects For Cancer Researchmentioning
confidence: 96%
“…The authors focused on the linker of nucleoskeleton and cytoskeleton (LINC) complex and showed that the nuclear shape and differential gene expression are both responsive to s-µg in a LINC-dependent manner [20]. Cytoskeletal changes were also detected in 3D multicellular aggregates when human chondrocytes were exposed to an RPM for 28 d [18]. The authors demonstrated that long-term µg created by RPM-induced 3D growth in human chondrocytes.…”
Section: Breast Cancer Cells In Microgravity: New Aspects For Cancer Researchmentioning
confidence: 99%